1991
DOI: 10.1152/ajpheart.1991.260.3.h1025
|View full text |Cite
|
Sign up to set email alerts
|

N omega-nitro-L-arginine selectively inhibits vasodilator responses to acetylcholine and bradykinin in cats

Abstract: The effects of N omega-nitro-L-arginine (nitroarginine), an inhibitor of endothelium-dependent relaxing factor (EDRF) production, on vascular tone and responses to vasodilator and vasoconstrictor agents were investigated in the hindquarters vascular bed of the cat. Under constant flow conditions, infusion of nitroarginine into the hindquarters vascular bed caused a significant increase in systemic arterial and hindquarters perfusion pressures. During infusion of nitroarginine, hindquarters vasodilator response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…These findings are consistent with those of others who have demonstrated a role for basal endogenous nitric oxide in the control of vasomotor tone throughout the body (21,22). Finding an intermediate baseline cerebral blood flow in the experiments in which L-arginine was added to the CSF containing L-NAME also supports a role for nitric oxide in control of basal cerebral blood flow.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with those of others who have demonstrated a role for basal endogenous nitric oxide in the control of vasomotor tone throughout the body (21,22). Finding an intermediate baseline cerebral blood flow in the experiments in which L-arginine was added to the CSF containing L-NAME also supports a role for nitric oxide in control of basal cerebral blood flow.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo studies have demonstrated increased baseline arterial pressure following systemic infusion of L-arginine analogues in rats (Gardiner et al, 1989), guinea-pigs (Aisaka et al, 1989), cats (Bellan et al, 1991) and dogs (Klabunde et al, 1990). Regionally, treatment with analogues of L-arginine have been found to increase vascular resistance in rabbit isolated hearts (Lamontagne et al, 1991), rabbit hindlimb (Mugge et al, 1991), dog hindlimb (White et al, 1993) and human forearm (Vallance et al, 1989).…”
Section: Basal No Releasementioning
confidence: 99%
“…Some studies have shown that the in vivo responses to endothelium-dependent agents are selectively inhibited by treatment with L-arginine analogues, while responses to endothelium-independent agents are not significantly decreased (Aisaka et al, 1989;Gold et al, 1989;Gardiner et al, 1989;Bellan et al, 1991;Kaley et al, 1992;White et al, 1993). Other studies, however, have shown either no decrease in responses to endothelium-dependent vasodilators (Mugge et al, 1991, Ross et al, 1991 or a non-selective inhibition of both endothelium-dependent and -independent vasodilatation (Thomas et al, 1989;Klabunde et al, 1990).…”
Section: Endothelium-dependent and -Independent Vasodilatationmentioning
confidence: 99%
See 2 more Smart Citations